Analysis and Quality Assessment of Refractories Formed under Reduced Pressure - Alicja Trela; Alena Pribulová; Peter Futas (Archives of Metallurgy and Materials, 2023)
Refractories are the basic material for the construction of the lining of a melting furnace used, among other things, in the foundry industry. The article describes a comparative study of the influence of the type of moulding on the quality of the finished refractory product. A method for making products from refractory materials was proposed and a test methodology was developed. The results, based on a classic study of the quality of these materials, confirm a strong influence on the quality of the materials obtained in terms of reduced porosity and homogeneity of pore size.